Geographic information system for boyolali tourist object mapping android based - Maria Atik Sunarti Ekowati; Kristyana Dananti; Darsini Darsini; Sri Wening (Jurnal Mandiri IT, 2023)
Boyolali is part of Indonesia which is rich in tourism potential and regional specialties. Boyolali is a city that has tourist attractions and typical regional souvenirs. Boyolali tourist attractions are New Selo, Gancik Hill, Kedung Kayang Waterfall, Omah Bammbu Merapi, Cengklik Reservoir, Gunung Madu Valley, Dairy Cow Agro Tourism, Brown Canyon, Tlatar Water Park, Mount Merbabu Trekking, Kedung Goro, Umbul Tirto, Gardens Raya Indrokilo, Bade Reservoir, Restu Wijaya Waterboom. However, there are problems for tourists outside the region due to the lack of information obtained or tourists' knowledge about where the tourist attractions they can visit are located. Apart from that, tourists are also confused about where to go. The aim of this research is to provide a solution to the problems faced by tourists by developing a geographic information system for mapping tourist attractions by utilizing the global positioning system (GPS) feature available on Android smartphones. Through the design of the application being developed, it is hoped that tourists and visitors to Boyolali tourist attractions will be able to obtain convenience in mapping tourist locations in the Boyolali area as well as help provide comments and ratings about the quality of the products produced by sellers.